Faktor Yang Mempengaruhi Kepuasan Pelanggan - Andonios Joel; Cario Marta (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2023)
Along with these developments, there has been intense competition in the hotel industry, which requires hotel management not only to rely on physical facilities but must be able to maximize their intangible assets. Management's ability to manage assets together is what differentiates a hotel from being superior to other hotels both in terms of innovation and performance because each hotel has different characteristics, resources and market share. Careful management will always make differentiation so that it can always meet a competitive advantage that is difficult for competitors to imitate.